R-Net grid monitoring and alarming system design - YAO Yuan-zhe1; DU Cui-lan2; LIU Xin-ran2; HE Miao3; WANG Zi-juan3; ZHANG Lu-wei1 (Tongxin xuebao)
By introducing the concepts,requirements,related standards and work of grid monitoring,some actual monitoring systems were analyzed;expounded the monitoring requirements and their relations,found some problems and deficiencies in grid monitoring.Based on the R-Net grid computing test platform,RNMS（R-Net monitoring system） used some technology such as adaptive sensor control,on-demand measurement,distributed directory service,node group management,mixed data format,which improved the interoperability and scalability,reduced the intrusiveness.Based on the RNMS,an alarming system was designed without more modifying.It shows the RNMS has a good scalability.